SUSTAINABILITY PERFORMANCE AND EARNINGS MANAGEMENT: THE ROLE OF BOARD MEETINGS - Jazman Jakeem; Amrie Firmansyah (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
Increasing attention toward sustainability disclosure has raised questions about whether Environmental, Social, and Governance (ESG) initiatives genuinely reflect corporate responsibility or are strategically utilized to obscure earnings management practices. This study employs a quantitative approach to examine the influence of ESG performance and intellectual capital on earnings management, while accounting for the frequency of board meetings as a moderating factor. The sample consists of 31 healthcare firms listed on the Indonesia Stock Exchange over the 2020-2024 period, yielding 109 firm-year observations selected using purposive sampling. The analysis relies on secondary data derived from audited annual reports and sustainability reports. To test the proposed relationships, the study uses unbalanced panel-data regression. The findings indicate that higher ESG disclosure is positively associated with earnings management, suggesting that sustainability reporting may be used as a strategic instrument for opportunistic financial reporting. In contrast, intellectual capital efficiency does not show a statistically significant relationship with earnings management. Furthermore, the frequency of board meetings enhances monitoring in the relationship between ESG performance and earnings management, but it does not influence the association between intellectual capital and earnings management.